Manifestations of Maqasid al-Shariah in Islamic Jurisprudence and Islamic Economics: An Epistemological Integration Perspective - Ming, Ni-abadee; Al-Usamah, Abdulloh; Haling, Huzaifah; Smahae, Saudin (MENARA : Journal of Islamic and Contemporary Issues, 2025)
This study aimed to conceptualize the fundamentals of Maqasid al-Shariah (the higher objectives of Islamic law) and highlight their influence on Islamic jurisprudence of transactions (fiqh al-mu‘amalat) and Islamic economics from the perspective of epistemological integration. The researcher employs both descriptive and analytical-critical methodologies to illustrate the manifestations of Maqasid al-Shariah across various legal and human dimensions. The study emphasizes that independent reasoning (ijtihad) and Islamic legal education cannot be adequately developed without integrating Islamic and human sciences. Maqasid al-Shariah hold a significant role in guiding intellectual reasoning, shaping legal adaptation, and demonstrating their effective function in three main areas: 1. Interpreting legal texts in light of the overarching objectives of Shariah, 2. Regulating the issuance of fatwas, and 3. Applying the principles of removing hardship and facilitating ease. The research further underscores the importance of a holistic outlook that connects Shariah with its purposes and outcomes—especially as reflected in contemporary ijtihad, the development of Islamic legal education, mechanisms of Islamic banking oversight, and the broader application of Shariah in alleviating harm and serving humanity at large.